2021
DOI: 10.3390/f12081040
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Strategies for the Management of Douglas-Fir in Central Europe

Abstract: In view of the increasing demand for forest resources in Europe, it is an option to foster the use of non-native tree species that can keep pace with the rapidly changing environmental conditions, such as Douglas-fir (Pseudotsuga menziesii). Thus, sufficient knowledge of how to manage such introduced species is highly required. In this study, we investigate theoretical silvicultural management options of Douglas-fir for forests in central Europe. We follow a three-step approach: (i) we collect the current cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Douglas fir originates from the Pacific Northwest of America and covers about 830,000 ha of forest land in Europe (Pötzelsberger et al, 2020). It is well investigated regarding biology, forest ecology, biodiversity, genetics, timber production, and timber quality as well as marketing (e.g., Podrázský et al, 2014;Schmid et al, 2014;Eckhart et al, 2017;Spiecker et al, 2019;Wohlgemuth et al, 2019;Eberhard et al, 2021). Various studies identified light supply on the forest floor, the composition and structure of understory vegetation, water availability, and the distance of diaspore sources as main factors for the natural regeneration of Douglas fir (Lavender et al, 1968;Broncano et al, 2005;Huth et al, 2011;Eggert, 2014;Eberhard and Hasenauer, 2018;Bindewald et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Douglas fir originates from the Pacific Northwest of America and covers about 830,000 ha of forest land in Europe (Pötzelsberger et al, 2020). It is well investigated regarding biology, forest ecology, biodiversity, genetics, timber production, and timber quality as well as marketing (e.g., Podrázský et al, 2014;Schmid et al, 2014;Eckhart et al, 2017;Spiecker et al, 2019;Wohlgemuth et al, 2019;Eberhard et al, 2021). Various studies identified light supply on the forest floor, the composition and structure of understory vegetation, water availability, and the distance of diaspore sources as main factors for the natural regeneration of Douglas fir (Lavender et al, 1968;Broncano et al, 2005;Huth et al, 2011;Eggert, 2014;Eberhard and Hasenauer, 2018;Bindewald et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The abundant natural regeneration of Douglas-fir has caused debate about the invasive potential of the species, although recent reports have considered that it is not invasive in Europe (Brus et al 2019). This categorization was supported by Eberhard and Hasenauer (2018), Bindewald et al (2021) and Lange et al (2022) based on the natural spread of the species being site-limited and easy to manage (e.g., Essl 2005;Ammer et al 2016;Raida 2018;Wohlgemuth et al 2019). However, in certain countries (e.g., Germany) there continues to be contrasting opinions about the species invasiveness (Thomas et al 2022).…”
Section: Douglasmentioning
confidence: 99%
“…Douglas-fir is mostly planted in spring (Austria and Germany: Eberhard et al 2021;Czech Republic: Podrázský et al 2019;Ireland: Horgan et al 2003;Romania: Ionescu 1963, Marcu andLiubimirescu 1979;Sweden: Malmqvist et al 2017). Survival rates of 70% − 80% or more can be obtained under good conditions, although failure rates tend to be higher than with some other conifers (Kohnle et al 2019).…”
Section: Plant Production Spacing and Early Establishmentmentioning
confidence: 99%
“…Based on the data presented, one viable solution to improving the economic perspective of forest owners and related wood processing industries is the controlled introduction of non-native tree species such as Douglas fir ( Eberhard et al, 2021 ) in Central Europe. The future use of these tree species must also be of long-term interest to the forest owner.…”
Section: Introductionmentioning
confidence: 99%
“…Douglas fir ( Pseudotsuga menziesii ) was defined as a potential candidate among different wood species. Douglas fir is already present in Europe and covers about 830,000 ha of forest area in Europe alone ( Pötzelsberger et al, 2020 ; Eberhard et al, 2021 ). These tree species offer high productivity rates and thus ensure sustainable income for forest owners ( Eilmann and Rigling, 2012 ).…”
Section: Introductionmentioning
confidence: 99%